Retraction Note to: Comparative analysis of the Corynebacterium glutamicum transcriptome in response to changes in dissolved oxygen levels. (1st March 2020) - Liu, Xiuxia; Yang, Sun; Wang, Fen; Dai, Xiaofeng; Yang, Yankun; Bai, Zhonghu
Abstract: The authors have retracted this article.